2017
DOI: 10.1002/jbio.201600209
|View full text |Cite
|
Sign up to set email alerts
|

Atherectomy using a solid‐state laser at 355 nm wavelength

Abstract: Peripheral arterial disease (PAD), caused by atherosclerotic processes, is allied with an increased risk of ischemic events, limb loss, and death. Recently, the use of a solid-state laser at 355 nm within a hybrid catheter was suggested for that purpose. In this work, short nanosecond pulses of a solid-state laser at 355 nm delivered through a hybrid catheter, composed of optical fibers and a blunt mechanical blade, are used to conduct a pre-clinical study and two clinical cases. The pre-clinical study consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A recent development by Herzog et al in delivering 355 nm ultraviolet (UV) ns pulses with high‐energy densities in optical fibers has opened up the possibility for new research and applications. An extension of this research showed the feasibility of using a hybrid catheter (composed of optical fibers and a blunt mechanical blade) delivering 355 nm pulses in atherectomy , for opening occluded blood vessels. The motivation for our work draws from the insight we gained when participating in human atherectomy clinical trials, whereby the human ear and brain could notice (to a certain extent) different sound signatures of lesion ablation vs non‐lesion ablation.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent development by Herzog et al in delivering 355 nm ultraviolet (UV) ns pulses with high‐energy densities in optical fibers has opened up the possibility for new research and applications. An extension of this research showed the feasibility of using a hybrid catheter (composed of optical fibers and a blunt mechanical blade) delivering 355 nm pulses in atherectomy , for opening occluded blood vessels. The motivation for our work draws from the insight we gained when participating in human atherectomy clinical trials, whereby the human ear and brain could notice (to a certain extent) different sound signatures of lesion ablation vs non‐lesion ablation.…”
Section: Introductionmentioning
confidence: 89%
“…The experimental setup for UV non‐thermal laser ablation acoustic measurements and analysis is presented in Figure . It consists of: (a) UV laser and catheter – fluence of 60 mJ/mm 2 per pulse, 355 nm wavelength, repetition rate of 40 Hz, 7 ns pulse duration, coupled to a 2 mm hybrid catheter, manufactured by Eximo Medical Ltd., Rehovot, Israel, made of 110 multi‐mode optical fibers of 70‐μ diameter core and 77‐μ diameter cladding with a numerical aperture of 0.22 and a blunt blade (shown in detail in Figure ); (b) Acoustic transducer—Benthowave BII‐7006, 0 to 100 kHz flat response hydrophone (impedance matched to a water medium); (c). Recording device—TASCAM DR‐100mkIII, 192 kHz; (d) Analysis programs—MATLAB and Tensor Flow.…”
Section: Methodsmentioning
confidence: 99%
“…Four catheter sizes (2.35 mm with off center alignment, 2.0, 1.5, and 0.9 mm) are available for treatment of FP and tibial arteries; the larger two catheters have an aspiration feature to limit procedural embolization. The system has approximately threefold higher affinity for atheroma than for endothelium and is indifferent to the presence of contrast material . The currently commercial B‐Laser™ system and catheters line are shown in Figures and , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of laser advancement in a bovine tendon model (simulating an atherosclerotic lesion) was 3‐fold higher than that into a blood vessel wall (with fluence of 60‐65 mJ/mm 2 per pulse), inherently aiming in increasing the safety profile of 355 nm laser by reducing risks for vessel injury in future atherectomy procedures. [ 1 ] Since then, a First in Man study (NCT02556255) including 50 subjects with a follow up of 1 year [ 2 ] and an IDE study, (NCT03157531) enrolling 97 Peripheral Artery Disease (PAD) patients (with a total of 107 lesions, 21.5% were chronic total occlusions [CTO]) treated with 355 nm laser atherectomy (Auryon, AngioDynamics Inc.), was conducted. The clinical results showed no major device‐related vascular complications requiring intervention in all patients with no emboli or perforations, [ 3, 4 ] and in the longer term, results showed excellent patency and clinical outcome at 6‐months [ 5 ] (with fluence of 50 or 60 mJ/mm 2 per pulse [ 2, 4 ] ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Since then, a First in Man study (NCT02556255) including 50 subjects with a follow up of 1 year [ 2 ] and an IDE study, (NCT03157531) enrolling 97 Peripheral Artery Disease (PAD) patients (with a total of 107 lesions, 21.5% were chronic total occlusions [CTO]) treated with 355 nm laser atherectomy (Auryon, AngioDynamics Inc.), was conducted. The clinical results showed no major device‐related vascular complications requiring intervention in all patients with no emboli or perforations, [ 3, 4 ] and in the longer term, results showed excellent patency and clinical outcome at 6‐months [ 5 ] (with fluence of 50 or 60 mJ/mm 2 per pulse [ 2, 4 ] ). Thus, the initial first time 355 nm laser ablation that was found to have “tissue selectivity” in ex vivo model, showed in two clinical studies results that support the tissue selectivity by high‐safety profile with high efficacy, including in severe calcification.…”
Section: Introductionmentioning
confidence: 99%